FUNGSI EVALUASI STRATEGI PEMBELAJARAN GURU UNTUK SISWA SEKOLAH DASAR - Alya Khoirunnisa Alya; Katni Katni (AL-ASASIYYA: Journal Of Basic Education, 2022)
This study aims to describe the importance of evaluating the learning strategies used by teachers in the learning process for upper elementary school students. Evaluation of learning strategies is necessary to determine the effectiveness of the methods, media, and approaches applied by teachers in achieving learning objectives. Upper grade students have more complex cognitive development characteristics, so the strategies used need to be tailored to their needs, interests, and abilities. By conducting systematic evaluations, teachers can identify the strengths and weaknesses of the strategies used, improve the learning process, and enhance student learning outcomes. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the evaluation of learning strategies plays an important role in promoting more effective, adaptive, and student-centered learning. In addition, continuous evaluation enables teachers to innovate learning that is more relevant to the needs of upper elementary school students.